A companion to John of Ruusbroec - Arblaster, John (Brill's companions to the Christian tradition, 2014)
John of Ruusbroec (1293-1381) is one of the most important mystical authors in the Christian tradition. This Companion provides a comprehensive overview of Ruusbroec studies, including a survey of the mystical tradition in the Low Countries before Ruusbroec, a discussion of his life and works, the manuscript tradition, the most significant mystical-theological and literary themes, Latin translations of his work, and the widespread resonance of his thought across Europe until 1800. Finally, it offers a summary of secondary research since the nineteenth century. To complement the range of scholarly articles, this Companion also includes the first English translation of a series of Middle Dutch texts that offer deeper insight into Ruusbroec, his thought, and his mystical and literary context. Contributors include: Jos Andriessen, John Arblaster, Guido De Baere, Rob Faesen, Bernard McGinn, Hilde Noë, Kees Schepers, Loet Swart, Rik Van Nieuwenhove, and Lieve Uyttenhove.